Kesadaran Dan Minat Masyarakat Muslim Membayar Zakat Melalui Badan Amil Zakat Nasional (BAZNAS Dharmasraya) - Amri Effendi; Risti Enjelia Putri (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Zakat is one of the Islamic economic instruments. Zakat is a sharia fiscal policy in Indonesia which has a strategic role in supporting the economy (Tinggi et al., 2024). Zakat is also a socio-economic instrument for the community to create social justice values through wealth redistribution, economic empowerment and poverty alleviation. This research aims to explore the low level of public interest in giving zakat and paying zakat through BAZNAS which occurs at BAZNAS Dharmasraya. As qualitative research, this article focuses on investigating an in-depth understanding of the lack of zakat muzakki through the Amil Zakat Institution. Data collection techniques through literature studies and interviews with BAZNAS. The research results show that: (1) The community does not yet have full awareness of zakat due to their still minimal understanding of the obligation to zakat; (2) Motivation to give zakat in society is influenced by their level of welfare because in recent years, the level of welfare in society has decreased due to the Covid-19 pandemic; (3) Zakat is distributed independently, such as assistance with education costs, cash assistance, and assistance in the form of business capital to underprivileged communities.